Penentuan Daur Optimal Jati Unggul Nusantara (JUN) di BDH Paliyan KPH Yogyakarta - Tatik Suhartati; Sugeng Wahyudiono; Nugroho Cahyo Wicaksono; Purwadi Purwadi (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2023)
Sustainable forest management requires planning forest management strategies that are based on growth and yield information. This information can be provided, among other things, through growth modeling. Therefore, the management of Jati Unggul Nusantara (JUN), which is the result of breeding Jati Plus Perhutani (JPP) trees, requires information about growth, yield and optimal cycles. The research aims to obtain a diameter growth model, free branch height, estimated volume and optimal volume cycle of JUN. Sampling was carried out using the systematic sampling method with random start. A total of 5 measuring plots were taken in each plot representing ages 3, 5 and 7 years. The parameters observed were diameter at breast height and free branch height. The models used are the Logarithmic Model, Inverse Model, and S Model. Model selection is carried out through model acceptance tests and validation tests. The model chosen to estimate the diameter at chest height of JUN is Model S with the equation Dbh = e(3.358 - 4.270/u). The model chosen to estimate the free branch height of JUN is Model S with the equation Tbc = e( 1,727 +( -3,100) /u. The optimal cycle of JUN in KPH Yogyakarta occurs at the age of 12 years and the volume obtained is 76,648 m3/ha. Key words : optimal cutting cycle, jati unggul nusantara, growth model